Adoption of Online Technologies for Language Teaching during COVID-19 Pandemic in Narrative Frames - Uun Muhaji; Didi Suherdi; Pupung Purnawarman (Universitas Pendidikan Indonesia, 2023)
Adopting and utilizing online technologies for emergency remote teaching during the COVID-19 pandemic is a requirement for most Higher Education Institutions (HEIs) in Indonesia in order to keep the pedagogical practice running. Having done the practice for about one year, it is paramount to have an understanding of teachers’ experience in their adoption of the technologies. Arguably, there has been zero study employing narrative frames conducted in Indonesia investigating EFL (English as a foreign language) university teachers’ experience in adopting online technologies for their teaching during the pandemic. Therefore, the present narrative study examines this issue. Four narrative frames were developed as the instruments of the study by referring to two core variables and one outcome variable of the Technology Acceptance Model (TAM) consisting of perceived ease of use, perceived usefulness, and reported general use of online technologies. 16 narrative frames completed by participants from seven universities in East and West Java unveil that despite the arduous initial process of shifting from face-to-face into online teaching, problems and difficulties which were still encountered during the pedagogical undertaking, and somewhat limited number of online platforms that had been utilized, the teachers’ very positive perceptions on the usefulness of online technologies led to persistence and optimism in their reported general use of the technologies in their teaching. It was concluded that teachers are quite ready to further implement online technologies in their teaching. However, supporting facilities, facilitating conditions, as well as training for developing technological knowledge and skills are needed to support the process.